THEORETICAL CONSIDERATIONS FOR DEVELOPING INTERCULTURAL SENSITIVITY THROUGH TRANSLATION ACTIVITIES: BEYOND THE MONOLINGUAL PREMISE IN FOREIGN LANGUAGE EDUCATION - Lankiewcz, Hadrian; Wąsikiewicz-Firlej, Emilia (Neofilolog, 2019)
The article presents theoretical considerations pertaining to the use of trans-lation in foreign language teaching and argues for the reinstatement of trans-lation activities in language teaching to contribute to the development of in-tercultural sensitivity among language users. The authors build upon critical-ecological reflections in language education. They posit that a globalized world requires a departure from the monolingual language teaching para-digm, particularly in multicultural and multilingual contexts such as, for ex-ample, a united Europe. The argument touches upon the issues of neoliberal skills training, intercultural education, language pedagogy (glottodidactics), language acquisition and translation theories as well as observations of the practicalities imposed on L2 users by the postmodern reality and market forces. The authors present the incorporation of translation practices into foreign language teaching as a means of enhancing intercultural sensitivity and a way of fighting linguistic and cultural colonization. The ultimate goal – the new “paradigm shift” (Butzkamm and Caldwell, 2009) – is to contribute to social justice via foreign language education.